The Nexus between Illegal Online Loans, Illegal Online Gambling, and the Rise of Sugar Daddy Phenomenon in Indonesia: The Nexus between Illegal Online Loans, Illegal Online Gambling, and the Rise of Sugar Daddy Phenomenon in Indonesia - Raden Aswin Rahadi (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2024)
This study investigates the interconnections between the rising instances of illegal online loans, illegal online gambling, and the prevalence of sugar daddy relationships in Indonesia. The research aims to explore how financial desperation, exacerbated by the COVID-19 pandemic, drives individuals towards these activities and the resulting socio-economic impacts. Utilizing a literature synthesis and content analysis of secondary data sources, including scientific articles, government reports, and media narratives, this study identifies common drivers and regulatory challenges. The findings reveal that economic hardship, lack of financial literacy, and cultural influences are key factors contributing to the proliferation of these phenomena. The study concludes with recommendations for comprehensive regulatory frameworks, public awareness campaigns, and strengthened social support systems to mitigate the adverse effects on Indonesian society.